2015
DOI: 10.1038/jcbfm.2015.101
|View full text |Cite
|
Sign up to set email alerts
|

Altered Contralateral Sensorimotor System Organization after Experimental Hemispherectomy: A Structural and Functional Connectivity Study

Abstract: Hemispherectomy is often followed by remarkable recovery of cognitive and motor functions. This reflects plastic capacities of the remaining hemisphere, involving large-scale structural and functional adaptations. Better understanding of these adaptations may (1) provide new insights in the neuronal configuration and rewiring that underlies sensorimotor outcome restoration, and (2) guide development of rehabilitation strategies to enhance recovery after hemispheric lesioning. We assessed brain structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(56 reference statements)
1
9
1
3
Order By: Relevance
“…32 Thus, experimental studies are also performed to better understand the mechanisms of neuroplasticity involved in the functional recovery of these patients. 28,29,34,45,49 We observed that animals submitted to experimental hemispherotomy displayed a motor deficit 10 days after the surgical procedures. However, there was a significant improvement in motor coordination and balance displayed by these animals in the rotarod test 30 days after the hemispherotomy, suggesting brain neuroplasticity.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…32 Thus, experimental studies are also performed to better understand the mechanisms of neuroplasticity involved in the functional recovery of these patients. 28,29,34,45,49 We observed that animals submitted to experimental hemispherotomy displayed a motor deficit 10 days after the surgical procedures. However, there was a significant improvement in motor coordination and balance displayed by these animals in the rotarod test 30 days after the hemispherotomy, suggesting brain neuroplasticity.…”
Section: Discussionmentioning
confidence: 91%
“…28,29,41 The functional recovery shown in the rats undergoing hemispherotomy in the present work is similar to that reported elsewhere. 19,34,53 In addition, the neurosurgical procedure preserved some critical connections subserving the motor function, such as the cortico-neostriatum-nigral pathways and the nigro-striatal projections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entretanto, por mais graves que sejam as consequências dessas lesões, podemos constatar que, frequentemente, ocorrem melhoras nos déficits funcionais. Essa recuperação pode ser observada em estudos experimentais realizados com modelos animais (Marino et al, 2001;Machado et al, 2003;Umeda e Funakoshi, 2014;Wanakhachornkrai et al, 2014;Otte et al, 2015).…”
Section: Investigação Comportamental (Teste Rotarod)unclassified